Characterization of noise exposure in places of worship. (September 2021) - Bellomo, Tiffany R.; Prasad, Sanjana; Abou-Hanna, Jacob; Talluru, Sai; Xie, Yanjun; Wang, Linyan; Green, Glenn E.; Neitzel, Richard L.
Highlights: Non-denominational Christian services assessed in this study exposed attendees to high noise levels. Over a quarter of measured noise levels were above recommended limits intended to prevent noise-induced hearing loss. Sound amplification systems used likely influenced noise exposure. Religious services may benefit from interventions to decrease noise exposure. Abstract: Background: The addition of concert instrumentation to contemporary religious services has exposed attendees to increased noise levels, which may contribute to noise-induced hearing loss (NIHL). Many smart device noise level measurement applications (apps) have been developed to assist in evaluation of noise exposure. However, there have been no published studies on noise exposure in American places of worship. Objective: We evaluated noise exposure in several different types of places of worship in Washtenaw County, Michigan, United States as well as the accuracy of smart device noise level measurement apps. Methods: Noise levels were measured at 26 services in 20 different places of worship using a combination of Spark 706RC dosimeters and iPod Touches running the US National Institute for Occupational Safety and Health (NIOSH) Sound Level Meter app. Dosimeters were programmed to measure according to the exposure limits recommended by the Environmental Protection Agency (EPA) for community noise and NIOSH for occupational noise. Relevant details on \ the services that could impact audience exposure to noise were recorded. Results: The mean equivalent continuous average exposure (LEQ ) level was significantly higher in audience measurements of Non-denominational places of worship in comparison to all other places (p = 0.004). Audience and podium LEQ levels were significantly higher if there were three or more vocal ensemble members (p = 0.001). No significant differences were noted between dosimeter and iPod LEQ levels. Roughly 35% of EPA measurements in the audience, 39% of EPA measurements at the podium, and 8% of NIOSH measurements at the podium exceeded the recommended exposure limits. Conclusions: A significant portion of measured services exceeded recommended noise exposure limits. The current results may support the need for additional noise exposure screening and potential noise reduction interventions in places of worship.